The Effect of Early Supplier Involvement on Firm Performance through Teamwork and New Product Development - Alvenia Oktapia; Zeplin Jiwa Husada Tarigan (Master of Management, School of Business and Management, Petra Christian University, 2022)
Manufacturing companies in Indonesia experienced the most severe growth due to the impact of the coronavirus pandemic (Covid-19). The effect of the pandemic resulted in companies reducing production capacity by reducing the use of utilities owned by the company. This study examines the effect of early supplier involvement on firm performance through teamwork and new product development. This research surveyed 55 companies from 104 manufacturing companies with more than 100 employees in East Java, Indonesia. The data collection used a questionnaire designed with a five-point Likert scale. Data analysis used SmartPLS version 3.0 to assess the measurement model and examine the hypothesis. This study developed nine hypotheses, which indicated that eight hypotheses were supported, and one hypothesis was rejected. Early supplier involvement affects teamwork, new product development, and firm performance. Furthermore, teamwork affects new product development and firm performance. Moreover, new product development affects firm performance. In addition, early supplier involvement indirectly affects firm performance through new product development and teamwork, respectively and simultaneously. These findings provide an insight for manufacturing management to consider early supplier involvement in developping new products and enhancing firm performance. This research will enrich the supply chain management theory, focusing on product development as the competitiveness of companies that are changing rapidly.